2011
DOI: 10.1111/j.1532-5415.2010.03286.x
|View full text |Cite
|
Sign up to set email alerts
|

Falls Incidence, Risk Factors, and Consequences in Chinese Older People: A Systematic Review

Abstract: Falls incidence in Chinese older people has been reported to be approximately half that of Caucasian populations. It is possible that the falls risk factor profile may differ significantly between Caucasian and Chinese populations, and a better understanding of this reported difference in incidence and associated risk factors may influence potential approaches to future intervention. A systematic literature review was conducted using the EMBase, Medline, Chinese Electronic Periodical Services, and WanFangdata … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
197
7
24

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(248 citation statements)
references
References 17 publications
20
197
7
24
Order By: Relevance
“…Kwan et al in their systematic review found that the median fall rates was 18%, they found that being complaining of fear of falling was commonly reported factor [10]. On the other hand, study by Leung et al did not match our findings as fear from fall was not significantly associated with falls [11], this contradictory could be due to the differences in the culture, habits and welfare between these two different societies.…”
Section: Discussioncontrasting
confidence: 57%
“…Kwan et al in their systematic review found that the median fall rates was 18%, they found that being complaining of fear of falling was commonly reported factor [10]. On the other hand, study by Leung et al did not match our findings as fear from fall was not significantly associated with falls [11], this contradictory could be due to the differences in the culture, habits and welfare between these two different societies.…”
Section: Discussioncontrasting
confidence: 57%
“…Other studies have suggested an age-related decrease of mechanoreceptors and consequently impaired proprioceptive traits [23,40,44]. Previous studies have also established a correlation between age and mechanoreceptor density [22,[36][37][38].…”
Section: Discussionmentioning
confidence: 99%
“…(3)(4)(5) Studies from a variety of contexts have reported that about 30% of older people experience at least one fall each year. (6) Furthermore, in the United States, approximately 30-50% of people living in long term care institutions fall each year, and 40% of them experience recurrent falls. (7) Falls are the cause of approximately 95% of all hip fractures among the elderly; 20% of elderly adults suffering from hip fractures die within a year following the incident.…”
Section: Introductionmentioning
confidence: 99%